Late cardiac perconditioning by phenylephrine in an isolated rat heart model is mediated by mitochondrial potassium channels - Afshin Nazari; Mehrnoosh Sedighi; Parvin Dalvand; Yaser Azizi; Maryam Moghimian; Shakiba Nasiri Boroujeni (Brazilian Journal of Pharmaceutical Sciences, 2019)
The present study was designed to investigate the effect of early and late administration of phenylephrine during ischemia against regional ischemia-reperfusion injuries in an isolated rat heart model. All animals were randomly divided into experimental groups: (I) IR (Ischemic/ reperfusion): the hearts underwent 35 min of regional ischemia followed by 60 min of reperfusion; (II) 5HD-IR-0: the hearts were perfused for 5 min with 5HD (5-hydroxydecanoate, specific mKATP channel blocker, 100 µM) at the onset of regional ischemia; (III) 5HD-IR-20: the hearts were perfused for 5 min with 5HD 20 min after regional ischemia; (IV) PE-IR-10: the hearts were perfused for 5 min with phenylephrine 10 min after regional ischemia; (V) PE-IR-30: the hearts were perfused for 5 min with phenylephrine (100 µM) 30 min after regional ischemia; (VI) PE-5HD-IR-10 group: the hearts were perfused for 5 min with 5HD at the onset of regional ischemia after which phenylephrine was administrated as in group IV; and (VII) PE-5HD-IR-30: the hearts were perfused for 5 min with 5HD 20 min after the ischemia and then phenylephrine was administrated as in group V. The hemodynamic parameters were recorded throughout the experiment. Ischemia-induced arrhythmias, myocardial infarct size (IS), creatin kinase-MB isoenzyme (CK-MB), plasma lactate dehydrogenase (LDH) activities, and coronary blood flow (CBF) were measured in all animals. Perfusion of phenylephrine 30 min after the regional ischemia curtailed the myocardial infarct size, reduced CK-MB, and improved cardiac function and CBF. Administration of 5HD 30 min after the ischemia abolished cardioprotective effects of phenylephrine in the late phase. These results suggest the involvement of mKATP in the mechanism of phenylephrine-induced late preconditioning.